Changing Substance Abuse and Criminal Behavior Through Therapeutic Relationships - Benveniste, Debra H.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book approaches the treatment process from a new and yet old perspective. Eleven men who successfully desisted from substance abuse and offending were interviewed to determine how their significant therapeutic relationships facilitated this life change. Data is integrated with a new psychodynamic framework, relational analytic theory, which focuses clinical attention on the qualities and processes of the therapeutic relationship. A therapy model is developed which addresses how to attain and maintain therapeutic engagement, treat client symptoms, and utilize therapeutic conflict to develop client capacity for internal conflict and personal agency, functions critical to resolving addictive behavior. Societal and cultural obstacles to treatment are addressed including group stigmatisation, a lack of funding, and our current manual and group-based treatment protocols.
Chapter 1. Introduction -- Chapter 2. The Men's Stories -- Chapter 3. Theoretical Context -- Chapter 4. Pathways to Desistance -- Chapter 5. Diagnostic Considerations -- Chapter 6. Developing a Practice Theory -- Chapter 7. Relational Therapy and the 'Real World'.
Keywords: Applied psychology; Forensic psychology; Consciousness; Rehabilitation; Psychotherapy and Counseling